Rates and Determinants of Retention on ART Among Orphans and Vulnerable Children Living With HIV in Tanzania - Charles, John; Exavery, Amon; Ally, Amal; Mseya, Remmy; Mbwambo, Tumainiel; Barankena, Asheri; Kyaruzi, Christina; Kikoyo, Levina (Frontiers in Public Health, 2022)
This study assessed the level of retention to antiretroviral therapy (ART) and its associated factors among OVC living with HIV (OVCLHIV) in Tanzania. Data were obtained from the USAID Kizazi Kipya project that collected pediatric ART data from October 2017 to October 2019 in 81 district councils of Tanzania. Community-based volunteers supported linkage and retention of the OVCLHIV on ART. Analysis of on-ART status was conducted in a cohort of OVCLHIV aged 0-20 years enrolled in the project and monitored for 24 months. OVCLHIV who remained on ART until the end of the follow up period were referred to as “retained”, otherwise “not retained”. Multivariable analysis was conducted using logistic regression, adjusting for baseline characteristics. From the 5,304 OVCLHIV analyzed, mean age was 13.1 years, 51.5% were female, and 72.2% were living with female caregivers. Their overall rate of retention on ART over the 24 months was 86.7%. Multivariable analysis showed that as higher frequency of home visit by the volunteer increased, the likelihood of retention increased by 8% (OR=1.08, 95% CI 1.06-1.11, p<0.001). Membership in PLHIV support groups was associated with higher likelihood of retention compared to non-membership (OR=3.31, 95% CI 2.60-4.21, p<0.001). Children in larger family size were 22% less likely to sustain ART (OR=0.78, 95% CI 0.72-0.84, p<0.001). Urban OVCLHIV were 18% less likely to remain on ART than their rural counterparts (OR=0.82, 95% CI 0.69-0.98, p=0.030). Remaining on ART was 49% more likely for OVC in economically better-off households than those in destitute families (OR=1.49, 95% CI 1.22-1.81, p<0.001). Male OVC were 17% less likely to be retained on ART than their female counterparts (OR=0.83, 95% CI 0.71–0.99, p=0.033). Community-based OVC support resulted in a high pediatric retention rate over the 24 months of follow up. While key enablers of retention were higher frequency of home visits by the project volunteer, participation in PLHIV support groups, and better economic status; large family sizes, urban residence, and male gender of the OVC were barriers. This study brings useful evidence to inform strategies for advancing retention of OVCLHIV on ART for their better health outcomes and overall wellbeing.